2010
DOI: 10.1007/s10463-010-0291-8
|View full text |Cite
|
Sign up to set email alerts
|

Minimal average degree aberration and the state polytope for experimental designs

Abstract: Corner cut, Design ideal, Factorial design, Latin hypercube sampling, Linear aberration, State polytope,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
(43 reference statements)
0
16
0
Order By: Relevance
“…We denote this generic size as n * and the quotient basis is said to be generic. Indeed, it was previously observed that a generic set of quotient basis exists at certain increments of n where the least aberration is observed [6]. If n is not generic, the quotient basis can be used to identify the polynomial accuracy of the algebraic quadrature but the confounding or aberration effects may have stronger influence on the accuracy of the algebraic quadrature.…”
Section: Univariate Uncertainty Quantificationmentioning
confidence: 99%
See 2 more Smart Citations
“…We denote this generic size as n * and the quotient basis is said to be generic. Indeed, it was previously observed that a generic set of quotient basis exists at certain increments of n where the least aberration is observed [6]. If n is not generic, the quotient basis can be used to identify the polynomial accuracy of the algebraic quadrature but the confounding or aberration effects may have stronger influence on the accuracy of the algebraic quadrature.…”
Section: Univariate Uncertainty Quantificationmentioning
confidence: 99%
“…At these n values, the quotient bases are generic and the design has the least aberration [6]. 4.5.2.…”
Section: 44mentioning
confidence: 99%
See 1 more Smart Citation
“…A study for the class of Latin hypercube designs carried out in Bernstein et al [2010] shows different situations that can occur when computing the algebraic fan. Moreover by Theorem 30 in Pistone et al [2001] for a design whose points are chosen at random (with respect to any Lebesgue absolute continuous measure) the algebraic fan equals the statistical fan with probability one.…”
Section: Motivations For a Numerical Fan Of A Designmentioning
confidence: 99%
“…In [12] the linear aberration for polynomial models is introduced. This is a new concept in experimental designs for quantitative factors which is an alternative to aberration and is strongly related to corner cut models and state polytopes.…”
Section: Advanced Topicsmentioning
confidence: 99%